Effectiveness of Brief Psychodynamic Therapy With Children and Adolescents: An Outcome Study - Michela Gatta; Marina Miscioscia; Marina Miscioscia; Lorenza Svanellini; Andrea Spoto; Manuela Difronzo; Maxim de Sauma; Emilia Ferruzza (Frontiers Media S.A., 2019)
Studies on the effectiveness of child and adolescent psychotherapy treatments provided by the Italian National Health Service lag behind, while the scientific community has rather focused on the value of cognitive-behavioral psychotherapeutic approaches. This paper evaluates the effectiveness of a one year psychodynamically-oriented intervention with children and adolescents-aged between 6 and 18 years (M = 12.08, SD = 3.7)-and their parents, carried out in a Child and Adolescent Neuropsychiatric Service (SCIAF), part of the Italian National Health System. Following a psychodiagnostic assessment, two types of therapeutic intervention were offered: children and adolescents allocated to Group 1 (N = 26) were offered individual psychodynamic psychotherapy alone, whilst youths in Group 2 (N = 31) were offered individual psychotherapy, accompanied by parental support. This study examines the effects of this time-limited (12 month) psychodynamically-oriented psychotherapy in terms of improvements in patients' symptoms (measured on the Achenbach's questionnaires: Child Behavior Checklist and Youth Self-Report 11-18). This study also examines the effects of treatment on parents' perception of their family empowerment. This domain is measured on the Family Empowerment Scale (FES). Our findings seem to be partly in line with published studies according to which poor parenting (i.e., characterized by lack of warmth, a rigid and/or negative parenting style, poor monitoring of the children, etc.) would be positively associated with Externalizing problems in childhood. Our preliminary findings suggest that brief psychodynamic therapy seemed to show positive outcomes in both "Internalizing" and "Externalizing" difficulties, accounting for age-related differences, ICD-10 (1) diagnoses, and the types of treatment offered. However, no statistically significant changes were detected in the parents' perceptions of empowerment at 12 months.